Laboratory Study on Corrosion Mechanism of Production System in In Situ Combustion - Haiyan Jiang; Shibao Yuan; Hao Wang; Boyi Wang; Jiao Wang (Geofluids)
The corrosion problem of a production system has been affecting the normal operation of an in situ combustion project. Because the environment of production system is significantly different in tubing, gas, liquid, and temperature in in situ combustion, the problem of the corrosion should be treated differently according to its origin. Based on the main environment of gas-liquid of the production system of in situ combustion, the corrosion of steel in N80 and J95, which are commonly used in oilfield, is studied in different temperature and pressure conditions. The results show that under the condition of 50°C and 3 MPa, the corrosion of the well is the most serious. Based on the analysis of corrosion causes in the production system, the corrosion under the protection of modified sacrificial anode in the liquid phase environment was studied. The results of comparative analysis show that the modified material had the dual protection effect of sacrificial anode and film-forming protection and could slow down the corrosion in different temperature ranges.